Effects of Typhoon Mangkhut on a Monsoon Evergreen Broad-Leaved Forest Community in Dinghushan Nature Reserve, Lower Subtropical China - Li, Yuelin; Mwangi, Brian; Zhou, Shun; Liu, Shizhong; Zhang, Qianmei; Liu, Juxiu; Chu, Guowei; Tang, Xuli; Zhang, Deqiang; Wei, Shimin; Lie, Zhiyang; Wu, Ting; et al. (Frontiers in Ecology and Evolution, 2021)
Compared to 2015, the difference between 2015 and 2018, only the tree height decreased significantly as a result of the typhoon. Therefore, we emphasized on the data collected in 2018 and 2020 in our analysis. The aim was to establish a scientific basis for the restoration of natural forests that have the ability to withstand strong weather phenomena such as typhoons. The results showed that trees that have a DBH of less than 5cm and a height of less than 2m are more prone to damage during a severe weather events. It is however worrying that in 2020, about 83% of all trees have a DBH of less than 5cm and an average height of 3.8m making up a large proportion of trees that could be destroyed or damaged if another storm occurred of similar or greater magnitude than the one that hit the region in 2018 especially since we established that taller trees having a height of greater than 20m and a DBH of more than 20cm faced minimal damage from typhoon Mangkhut. A correlation between the number of trees per hectare and the DBH showed a trend line that underlines the vulnerability of the tree population in the forest to the whims of the weather. The correlation between DBH and tree height illustrated that a tall tree will also have a larger DBH and will therefore be able to hold its ground when nature comes with full force like it did in 2018. Also, of interest was the forests remarkable ability to bounce back because, when the total above ground dry weight is compared between the year 2018 and the year 2020, the forest shows in increase in biomass. It is therefore of utmost importance that strategies be put in place to protect this ecosystem by employing the use of natural forests that have great resiliency against typhoons and construction of artificial forests that act as a buffer against dangerous weather.